THE COMPARATIVE AND HEALTH RISK ASSESSMENT OF HEAVY METALS IN SOME LOCAL AND FOREIGN LIPSTICK BRANDS SOLD IN DOMESTIC AND INTERNATIONAL MARKETS: A RECENT REVIEW - Rukayya, Muhammad Nuradeen; Abubakar, Lawal (FUDMA Journal of Sciences, 2025)
Heavy metals such as lead (Pb), cadmium (Cd), arsenic (As), and mercury (Hg) are toxic, non-biodegradable substances that pose significant health risks through bioaccumulation. Their presence in cosmetics, particularly lipsticks, which are semi-ingested during use, is a major public health concern. Long-term exposure to these metals is linked to neurotoxicity, renal dysfunction, endocrine disruption, and carcinogenic effects. While numerous international and regional studies in Southern Nigeria have documented alarming concentrations of these metals in cosmetics, a significant empirical data gap exists for Northern Nigeria, specifically Katsina State. This review synthesizes existing literature to highlight the prevalence, concentration ranges, and associated health risks of heavy metals in lipsticks globally and within Nigeria. Findings reveal recurrent exceedances of international safety limits (e.g., US FDA, WHO) in various markets, with Pb and Hg being the most critical contaminants. The absence of localized data for Katsina impedes effective regulatory enforcement by bodies like NAFDAC and SON and leaves consumers vulnerable. This review underscores the urgent need for original research in Katsina to quantify heavy metal levels in commonly sold lipstick brands, conduct a science-based health risk assessment, and provide evidence for robust public health interventions and policy formulation to ensure consumer safety.
Keywords: Heavy Metals; Lipstick; Health Risk Assessment; Public Health; Katsina State